Thin, Flexible Supercapacitors Made from Carbon Nanofiber Electrodes Decorated at Room Temperature with Manganese Oxide Nanosheets. (8th September 2013) - Nataraj, S. K.; Song, Q.; Al-Muhtaseb, S. A.; Dutton, S. E.; Zhang, Q.; Sivaniah, E.
Abstract : We report the fabrication and electrochemical performance of a flexible thin film supercapacitor with a novel nanostructured composite electrode. The electrode was prepared by in situ coprecipitation of two-dimensional (2D) MnO2 nanosheets at room temperature in the presence of carbon nanofibers (CNFs). The highest specific capacitance of 142 F/g was achieved for CNFs-MnO2 electrodes in sandwiched assembly with PVA-H4 SiW12 O40 · n H2 O polyelectrolyte separator.